Research on the development trend of global running protection equipment technology from the perspective of patent measurement - Qiong Shen; Yao Liu; Lei Qiang (PLoS ONE, 2026)
This study provides a systematic examination of global development trajectories in running protective equipment by applying large-scale patent mining and quantitative analysis to international and domestic patent data. The results identify three distinct phases in the evolution of this field: the nascent stage (1898–1970), the accumulation period (1971–1999), and the rapid expansion phase after 2000. Patent activity has been dominated by enterprises in the United States, which maintain a leading position in both volume and quality, while China has demonstrated rapid growth in filings since the early 2000s, gradually enhancing its international visibility despite a comparatively late entry. Analysis of patent validity indicates that only 34.47% of patents remain active, with more than half lapsing within a relatively short time frame. This pattern reflects limited incentives for long-term maintenance and reveals structural weaknesses in sustaining technological outputs. Furthermore, the technological evolution analysis shows a pronounced concentration of innovation in three domains—running shoes, sportswear, and knee pads—while diversification into emerging areas such as advanced materials and intelligent features remains underdeveloped. This imbalance, defined by low durability and narrow domain coverage, constrains commercialization potential and reduces the economic viability of many patented inventions. Core patent screening using a TOPSIS-based model demonstrates that high-quality patents are concentrated in a small number of enterprises and IPC subclasses, underscoring the uneven distribution of technological impact and market potential across the industry. Key technological trajectories are characterized by advances in sole stabilization and cushioning systems, optimization of textile structures and stitching techniques, integration of protective elements into apparel, and improvements in the structural and cushioning design of knee pads, with gradual progression toward material-enhanced and intelligent applications. These findings provide an evidence-based framework for understanding the global dynamics of running protective equipment technology and offer critical insights for guiding industrial upgrading, patent management strategies, and policy design aimed at fostering sustainable innovation and commercialization in this sector.